Geospatial Intelligent Analysis to Support Indonesian Airspace Defense - Rahmandhala, Ilvan Dino; Supriyadi, Asep Adang; Prihanto, Yosef; Samingan, Muhammad; Gultom, Rudy Agus Gemilang (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study highlights the importance of Geospatial Intelligence (GEOINT) analysis in supporting Indonesia's airspace defense. In modern military operations, especially air defense, the role of GEOINT is crucial as it enables real-time detection, mapping, planning, surveillance, and analysis of aerial threats. This research aims to analyze the role and potential of GEOINT in supporting Indonesia's airspace defense and to provide strategic recommendations for strengthening air defense. The findings of this study are expected to guide policymakers in enhancing the effectiveness and efficiency of air defense through the use of GEOINT, as well as supporting the development of necessary geospatial infrastructure. This study employs the SEIM (Sensor Effector Information Management) hierarchical approach to integrate various data sources and analytical tools to enhance detection, mapping, planning, and surveillance capabilities in the context of air defense. The study finds that GEOINT enables deeper tactical and strategic situation analysis and can optimize weapon assignments to increase efficiency in military conflicts. To effectively implement GEOINT, investments in technology, data infrastructure development, personnel training, and international cooperation are necessary. The implementation of remote sensing satellites capable of providing real-time, high-resolution imagery will enhance threat detection and monitoring capabilities.